Evaluación de riesgo por sismo en el centro histórico de Huaraz, distrito de Huaraz, Huaraz - Ancash - Aranda Leiva, Ruben Dario (2023)
The objective is to identify the hazard, vulnerability and risk in the historic center of Huaraz due to the occurrence of an earthquake. Through the use of the manual for the evaluation of risks originated by natural phenomena in its second version prepared by the National Center for Disaster Risk Estimation, Prevention and Reduction (CENEPRED) it was possible to determine the levels and maps of hazard, vulnerability and risk. Once the field work was carried out, it was possible to obtain information on the factors, conditioning factors and triggers that were related by the multi-criteria method for a semi-quantitative analysis, which will influence the 152 lots evaluated, so it was found that 70 lots present a level of hazard very high and 82 lots present a high level of hazard. In addition, it was determined that 55 lots have very high vulnerability, 84 lots have high vulnerability and 13 lots have medium vulnerability. The overlap of the hazard map and the vulnerability map determined the risk, finding that 37% of lots are at very high risk and 63% of lots are at high risk.